Priročnik za delo s programom PIPEOPT-SR za optimiranje visokotlačnih jeklenih cevovodov z ojačitvami - Kravanja, Stojan; Žula, Tomaž (University of Maribor Press, 2024)
Manual for Working With the Pipeopt-Sr Program for Optimizing High-Pressure Steel Pipelines With Reinforcements. This manual deals with the work with a program - an optimization model - for the optimization of high-pressure steel penstocks with stiffener rings, as they are installed in a tunnel bored into a rock. The penstock is dimensioned as a self-supporting steel cylindrical shell with circular stiffener rings without the assistance of the surrounding concrete and rock. The penstock can be loaded with internal or external pressure. Penstock optimization is performed using non-linear programming, NLP. For this purpose, the optimization program PIPEOPT-SR, version 1.0, was modeled. The optimization program contains scalars (input data), variables and a mass objective function of the steel structure, subjected to a system of (in)equality constraints from the static analysis and dimensioning of the pipeline according to the C.E.C.T. Recommendations. At the end of the manual, an example of optimization of the high-pressure penstock with stiffener rings of the Pump Hydropower Plant Kozjak near the city of Maribor is presented.